PSYCHO-B`GREAT MODULE: UTILIZING NGT TO DEVELOP HEURISTIC ASSESSMENT STRATEGIES - Saidatul Ainoor Shaharim; Nor Asniza Ishak; Rozniza Zaharudin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study evaluates Malaysian lecturers' perceptions of a prototype Mobile Game-Based Learning (mGBL) application using a heuristic assessment strategy through the Nominal Group Technique (NGT). The objective is to assess the usability and effectiveness of the Psycho-B`GREAT Module in higher education. A qualitative approach was employed, where five educators evaluated four key components: Game Usability (GU), Mobility (MO), Game Playability (PL), and Learning Context (LC). The assessment process involved structured discussions and consensus-building through NGT. Findings indicate high acceptance, with game control flexibility (100%) and help availability (100%) receiving the highest ratings. Additionally, learning content provision and content understandability both scored 100%. However, concerns included stigma (85.71%), lack of understanding (90.48%), and fear of evaluation (95.24%). These findings highlight the need for systematic strategies to enhance mobile learning effectiveness and support the broader integration of game-based learning in education.